Pathological Hyperinsulinemia and Hyperglycemia in the Impaired Glucose Tolerance Stage Mediate Endothelial Dysfunction Through miR-21, PTEN/AKT/eNOS, and MARK/ET-1 Pathways - Liu, Ran; Guan, Shilin; Gao, Zhongai; Wang, Jingyu; Xu, Jie; Hao, Zhaohu; Zhang, Yi; Yang, Shaohua; Guo, Zhenhong; Yang, Juhong; Shao, Hailin; Chang, Baocheng (Frontiers in Endocrinology, 2021)
Background Impaired glucose tolerance (IGT) is an important prediabetic stage characterized by elevated concentrations of glucose and insulin in the blood. The pathological hyperglycemia and hyperinsulinemia in IGT may regulate the expression of microRNA-21 (miR-21) and affect the downstream insulin signaling pathways, leading to endothelial cell dysfunction and early renal damage. Methods The individual and combined effects of insulin and glucose were investigated using human glomerular endothelial cells (HGECs). The expression levels of miR-21, and PTEN/AKT/eNOS and MAPK/ET-1 pathway proteins in the treated cells were measured. The levels of nitric oxide (NO) and endothelin-1 (ET-1) secreted by the cells were also measured. The role of miR-21 in mediating the regulatory effects of insulin and glucose was assessed by overexpression/inhibition of this miRNA using mimics/inhibitor. Results High (>16.7 mmol/L) concentration of glucose upregulated the expression of miR-21, leading to the activation and inhibition of the PTEN/AKT/eNOS and MAPK/ET-1 pathways, and upregulation of NO and downregulation of ET-1 secretion, respectively. High (>25 ng/mL) concentration of insulin downregulated the expression of miR-21, and lead to the activation of the MAPK/ET-1 and inhibition of the PTEN/AKT/eNOS pathway, thereby upregulating the expression of ET-1 and downregulating the secretion of NO. MiR-21 was observed to play a key role by directly controlling the activation of the insulin signaling pathways when the cells were cotreated with different concentrations of insulin and glucose. The expression of miR-21 was found to be dependent on the relative concentration of insulin and glucose. Under simulated conditions of the IGT stage (8.3 mmol/L glucose + 50 ng/mL insulin), the inhibitory effect of high insulin concentration on miR-21 expression in the cells attenuated the activation by high glucose concentration, resulting in the downregulation of miR-21, upregulation of ET-1 and downregulation of NO secretion. Conclusion Taken together, these results indicate that high insulin and glucose concentrations regulate the secretory function of glomerular endothelial cells in opposite ways by regulating the expression of miRNA-21. Pathological concentrations of insulin and glucose in the IGT stage may lead to a decrease in miR-21 expression, thereby disordering the secretion of vasoactive factors, resulting in renal tubule ischemia.